The Role of Emotional Competences in Parents’ Vaccine Hesitancy - Teresa Gavaruzzi; Marta Caserotti; Irene Leo; Alessandra Tasso; Leonardo Speri; Antonio Ferro; Elena Fretti; Anna Sannino; Enrico Rubaltelli; Lorella Lotto (Vaccines, 2021)
The role of parents’ emotional competencies on vaccine hesitancy and decision making has been seldom examined. Two studies investigated the relationship between parents’ attitudes towards childhood vaccines and self-reported behavior (Study 1) and between parents’ emotional competence and attitudes towards vaccines (Study 2). In Study 1, predictors of temporal, partial, or complete vaccine refusal (having voluntarily postponed/forgone some/all vaccines) were examined in 2778 parents. In Study 2, psychological predictors of the attitude towards vaccines were examined in 593 parents, using the Profile of Emotional Competence and the valence of mental images spontaneously associated with the term “vaccine”. In Study 1, attitudes were aggregated in three independent factors (concerns about vaccine safety; diseases prevented by vaccines; and naturalistic views) that independently predicted vaccine refusal. In Study 2, a significant mediational analysis showed a positive indirect effect of intrapersonal emotional competences on attitudes towards vaccines, through mental images associated with the word “vaccine”. Parents’ intrapersonal emotional competences affected all dimensions of attitudes towards vaccines, suggesting that being able to manage, identify, and recognize one’s own emotions is central to vaccine acceptance. These findings suggest that intervention strategies, rather than stressing the pro-social benefits of vaccinating, should focus on aspects related to one’s own emotions.